Pengendalian Kualitas Pada Mesin Injection Moulding Dengan Menggunakan Metode Mil Std 105d Dan Mil Std 414d Pada PT Cicor Panatec Batam - Erik Gowasa; Nofriani Fajrah (Prosiding, 2019)
Nowadays,the development of industry is increasing very rapidly. It can be knownasthe high competition between companies. Not only large and international scaled companies, small and medium-sized companies are also face the same challenges in theglobal competition. Based on the preliminary study it is known that quality control is only done within the checking limit of the number of defective products produced without being evaluated or analyzed further. It is therefore necessary to analyze the defect product data generated and evaluate the results. The purpose of this study was to analyze the incompatibility of Comb 1 mm products. Map p is used in this study to analyze the number of defective products. Then a fishbone diagram is used to analyze the cause of product nonconformity. The results showed that there were no data within the control limits and most of the products were out of the median line of the P control chart. From the fishbone diagram found that human factors, machinery, raw materials, methods, and environment are the causes of mismatch comb products 1 mm. This research is expected to be useful for companies to improve product quality and customer satisfaction.